Unialgal culture of Pseudonitzschia (Bacillariophyceae) species a Domoic Acid (AD) toxin producer, local of Oman Sea - S, Kamali; F., Noghani (International Journal of Aquatic Research and Environmental Studies, 2022)
Fish and other aquatic foods are a key part of global food systems and a highly nutritious food group of major social, cultural, and economic significance. Like meat processors and farmers, the seafood sector has been significantly affected by the COVID-19 pandemic. Fishing fleets were tied up, and fish farmers faced an ever-increasing biomass in their cages, ponds, and tanks. Transport links all over the world were severed, restaurants closed, and supermarkets either abandoned or reduced their fresh seafood offerings. Disruptions in supply chains for fish and aquatic foods occurred due to interruptions in transportation, trade, and labor. Falling production from reduced fishing efforts and delayed stocking of aquaculture systems led to lower supplies, access, and consumption of these foods. Decreased consumer demand and increased transaction costs had a knock-on effect that pushed the prices of fish and aquatic foods upward, making them less affordable for poor consumers. Many people employed in these supply chains, such as fish vendors, processors, suppliers, and transport workers, lost their jobs. Demand for packaged and frozen products spiked as households looked to stock up on non-perishable food at the expense of fresh seafood options. Other consequences of the virus outbreak included the cancellation of key seafood trade events across the world and delays in aquaculture harvests due to labor shortages. In general, the effects of COVID-19 on the seafood market included a drop in seafood demand amid restaurant closures, a rise in salmon exports to Europe and the US despite increased logistic costs, a decline in cod sales, a shift from fresh to frozen fish in several markets, increased sales of packaged food across Europe as COVID-19 cases rose, and major disruptions in supply chains for fish and aquatic foods caused by interruptions in transportation, trade, and labor.